Rice DST transcription factor negatively regulates heat tolerance through ROS-mediated stomatal movement and heat-responsive gene expression - Ding, Yanfei; Zhou, Mei; Wang, Ke; Qu, Aili; Hu, Shanshan; Jiang, Qiong; Yi, Keke; Wang, Feijuan; Cai, Chong; Zhu, Cheng; Chen, Zhixiang (Frontiers in Plant Science, 2023)
Plants are frequently subjected to a broad spectrum of abiotic stresses including drought, salinity and extreme temperatures and have evolved both common and stress-specific responses to promote fitness and survival. Understanding the components and mechanisms that underlie both common and stress-specific responses can enable development of crop plants tolerant to different stresses. Here, we report a rice heat stress-tolerant 1 (hst1) mutant with increased heat tolerance. HST1 encodes the DST transcription factor, which also regulates drought and salinity tolerance. Increased heat tolerance of hst1 was associated with increased reactive oxygen species (ROS) as a result of suppressed expression of ROS-scavenging peroxidases and reduced water loss due to decreased stomatal aperture under heat stress. These mechanisms are similar to those in the drought and salt stress tolerance. However, increased heat tolerance of hst1 was also associated with enhanced induction of heat shock genes. Furthermore, mutation of HST1 improved reproductive traits including pollen viability and seed setting under high temperature. These results broaden the roles of DST in abiotic stress tolerance and provide important new insights into DST-regulated tolerance to diverse abiotic stresses through both shared and stress-specific mechanisms.